Political Party Systems in Britain and America: Comparative Study - ابتسام، قريشة, مريم، بلباسي (University of El-oued, 2022)
ينبثق مفهوم النظام الحزبي من العلوم السياسية المقارنة التي تناول فيها الباحثون النظام الحزبي في الولايات المتحدة واستخدموه لدراسة الأنظمة الأخرى. تهدف هذه المذكرة إلى دراسة شكل الأحزاب السياسية والنظام الحزبي في بريطانيا والولايات المتحدة الأمريكية، واستكشاف أوجه التشابه والاختلاف بينهما، وهو ما قد يكون مفيدًا لطلاب العلوم السياسية وأي شخص مهتم بالموضوع. الدراسة عبارة عن بحث نوعي يعتمد على المنهج التحليلي التاريخي والذي تم من خلال التطرق للأحداث والحقائق التاريخية لطرفي الدراسة المقارنة. النتائج المتوصل إليها قد تدفع إلى إعادة التفكير في نظام الحزب في المملكة المتحدة. كما أنها توضح بدرجة أكبر أن المملكة المتحدة لديها نظام ثنائي الحزب ولكن لا يتم التعبير عنه كنظيره في أمريكا. والسبب وراء ذلك يكمن في نظام التصويت المعتمد في الانتخابات العامة " نظام التصويت الفائز يأخذ الكل". لذلك، فإن البريطانيين يطالبون بنظام تصويت أكثر تمثيلية والذي إذا تم تطبيقه، فستكون الأمور مختلفة. في أمريكا، على الرغم من نظام الحزبين الثابت، قد يؤدي التداخل بين الحزبين السياسيين الرئيسيين في النهاية إلى نظام الحزب الواحد The concept of the party system emerges from comparative political science in which scholars examine party system in the United States and use it to study others. This dissertation is intended to investigate within the above framework political parties and party system in Britain and America, and to explore the similarities and the differences between them. This would be very helpful for students of political sciences and anyone who is interested in the topic. The study is a qualitative research based on the historical analytical method through which historical events and facts of the two sides of the equation are depicted. The findings prompt a re-thinking of the United Kingdom party system. They also illustrate to a larger degree that the United Kingdom does have a two party system that it is not pronounced as its counterpart in America. The reason behind this lays on the First Past the Post voting system. However, the disgruntlement of the British calls for more representative voting system which if it was applied, things would be different. In America, despite the steady two- party system, the overlap between the two major political parties may lead eventually to one-party system.
Keywords: الأحزاب السياسية، نظام الحزب، نظام الحزب الواحد، نظام الحزبين، نظام التصويت الفائز يأخذ الكل، نظام التصويت النسبي.; First Past the Post, one- party system, party system, political parties, proportional voting system, two- party system